Práctica previa odontológica de un caso clínico en simulación háptica antes del tratamiento en el paciente - Chávez-Alayo, Pablo (2024)
This descriptive and cross-sectional study addressed students' perceptions of a preliminary practice in dental preparation for a metal-free crown, conducted on the same clinical case using haptic simulation before patient treatment. The sample consisted of 6 final-year dentistry students who, using haptic simulation with scanned images of the same patient's mouth, prepared metal-free crowns prior to treating the patient. Data collection was carried out through two surveys. It was found that 66.7% (n=4) of the students considered this experience very useful, and 83.3% (n=5) mentioned that the experience provided them with confidence to perform the procedure on the patient. The results suggest that recurrent practice in haptic simulation of a clinical case, prior to patient treatment, is favorable for performance and provides greater confidence in carrying it out.